If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 9x + -22 Reorder the terms: x = -22 + 9x Solving x = -22 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. x + -9x = -22 + 9x + -9x Combine like terms: x + -9x = -8x -8x = -22 + 9x + -9x Combine like terms: 9x + -9x = 0 -8x = -22 + 0 -8x = -22 Divide each side by '-8'. x = 2.75 Simplifying x = 2.75
| X+2x-4x=41 | | -65-12x=65-7x | | 2w^2+9w+0=0 | | 7n-4(-3n+4)= | | P(p+3)=2(p+3) | | 6x-6-3x=5x+10 | | 7(x-6)=79 | | 0.5T+4.1=5.7-0.3 | | 23-6x=41 | | x-16+(-24)=7 | | 5z=-3(x+7) | | 1.2m-12cm= | | 6a+1=27 | | 35=5x+6-10 | | 8x-(8+6x)=-16 | | -46-2x=-7x+104 | | 3[2x-2-x]=5x+10 | | 3x-5=48+40x | | -10w+9=-6 | | e+25-32=8 | | 6.5n=110.5 | | Y-10.8=45 | | 3x-5=-48+40x | | 5y+2=5y+4 | | 2e+7-4e=15 | | n-20.39=-3.39 | | 3[2(x+1)-x]=5(x+2) | | 10+10r=8r+4 | | 3(2n-5)-9=30 | | z-49+45=-4 | | -4(r+9)=-74 | | x^2-10x+y^2-20y=125 |